White collar. The complete fourth season [videorecording (DVD)]. - DeKay, Tim, 1963-; Bomer, Matthew, 1977-
White Collar centers on the doubtful crime-solving partners Neal Caffrey, a charming ex-con, and Peter Burke, the Federal Agent charged with keeping him in order.